ANALISIS PENERAPAN PERAWATAN MOTOR KONVEYOR MESIN XRAY DENGAN MENGGUNAKAN METODE RELIABILITY CENTERED MAINTENANCE (RCM) PADA PT. TRISTAN ENGINEERING - Joko Purnomo; Naufal Affandi; Asep Rahmatullah (LPPM Universitas Bina Bangsa, 2021)
PT. Tristan engineering is a company engaged in services and goods. This company provides services and procurement of goods or spare parts needed by other companies. The X-ray machine moves 165 rpm for 24 hours non-stop in checking the goods that come in and out of the company. In this situation, the damage can occur at any time and can cause uncertainty about the availability of the machines to support the checking process. This research aims to determine the application of the system and the benefits of the Reliability Centered Maintenance system on the application of maintenance of the x-ray machine conveyor motor. The research method used is the Reliability Centered Maintenance method, which is used to reduce downtime that occurs in PT. Tristan Engineering. The research results were obtained at PT. Tristan Engineering includes the absence of periodic maintenance, causing damage to the x-ray engine components. From the results of the improvement of the proposed conveyor motor maintenance application, the occurrence of downtime is caused by the identification of the failure to detect the severity value, occurrence, and detection of each component of the discussion and conclusion described using the FMEA method is 683 RPN, it must be done machine maintenance periodically. From the planning effort of Reliability Centered Maintenance accompanied by a comparative analysis, the proposed improvements can reduce the average downtime by 39% on the problems of each component accompanied by MTBF 2.412 hours